2020
DOI: 10.3390/su12145547
|View full text |Cite
|
Sign up to set email alerts
|

Online Company Reputation—A Thorny Problem for Optimizing Corporate Sustainability

Abstract: The new economic environment, characterized as volatile, uncertain, complex, and ambiguous, has been generated through the evolution of a world in which online reputation and corporate social responsibility have become closely interconnected. In this study, we assessed whether corporate social responsibility is a goal with multiple implications for the image of the organization and its financial results, which present a model for measuring online reputation in the context of optimizing corporate sustai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 72 publications
(109 reference statements)
1
7
0
2
Order By: Relevance
“…The image of a company can also be tarnished if their goods or services are faulty and detected by current and prospective clients and other actors. Reputational threats can be calculated by analyzing incidents that are likely to lead to an inability to fulfill customer expectations and then determine their probability [48].…”
Section: -Literature Reviewmentioning
confidence: 99%
“…The image of a company can also be tarnished if their goods or services are faulty and detected by current and prospective clients and other actors. Reputational threats can be calculated by analyzing incidents that are likely to lead to an inability to fulfill customer expectations and then determine their probability [48].…”
Section: -Literature Reviewmentioning
confidence: 99%
“…Através da incorporação de modelos sustentáveis de gestão, é possível impulsionar a criação de vantagem competitiva (BOCKEN et al, 2014;ONCIOIU et al, 2020, SOBROSA NETO et al, 2020. Além disso, a sustentabilidade corporativa pode ser um meio eficaz para construir a confiança das partes interessadas e estruturar a sua reputação no mercado (ONCIOIU et al, 2020;RICCI et al, 2020;TUNI, RENTIZELAS;CHINESE, 2020) além de aumentar o valor agregado das ofertas e diminuir o risco percebido pelo cliente (ONCIOIU et al, 2020). Ainda nesse sentido, Tseng, Lim e Wu (2018) também descobriram uma melhoria na imagem da organização, o que proporcionou alívio das incertezas das ofertas e aumento da satisfação do cliente.…”
Section: Sustentabilidade Corporativaunclassified
“…Nesse sentido, instituições não governamentais (WANNAGS; GOLD, 2020), regulamentações dos governos (SOBROSA NETO et al, 2020), a pressão dos próprios consumidores (TSENG; LIM; WU, 2018; PAIVA; GIESTA, 2019;) ou ainda, a busca pela melhoria da reputação corporativa, conforme destacado por Oncioiu et al (2020), têm exigido que as empresas assumam a responsabilidade diante da sociedade e do meio ambiente, da mesma forma com que priorizam relações estreitas com os aspectos econômicos. Em outras palavras, independentemente dos motivadores, a atenção deve estar voltada aos benefícios sociais, ambientais e econômicos decorrentes dessa mudança nos modelos de gestão.…”
Section: Sustentabilidade Corporativaunclassified
“…Moreover, social media can have notable effects on group-level strategic endeavor, which cannot be avo ided in order to get success in this modern and competitive environment. Oncioiu et al, (2020) studied that online reputation is a dynamic process for every organization, country or political party. It is found that online reputation plays a vital role in failure and success of the organization or political party.…”
Section: Online Reputation Managementmentioning
confidence: 99%